No iron fertilization in the equatorial Pacific Ocean during the last ice age - Costa, K. M.; McManus, J. F.; Anderson, R. F.; Ren, H.; Sigman, D. M.; Winckler, G.; Fleisher, M. Q.; Marcantonio, F.; Ravelo, A. C. (Nature, 2016)
The equatorial Pacific Ocean is one of the major high-nutrient, low-chlorophyll regions in the global ocean. In such regions, the consumption of the available macro-nutrients such as nitrate and phosphate is thought to be limited in part by the low abundance of the critical micro-nutrient iron1. Greater atmospheric dust deposition2 could have fertilized the equatorial Pacific with iron during the last ice age—the Last Glacial Period (LGP)—but the effect of increased ice-age dust fluxes on primary productivity in the equatorial Pacific remains uncertain3, 4, 5, 6. Here we present meridional transects of dust (derived from the 232Th proxy), phytoplankton productivity (using opal, 231Pa/230Th and excess Ba), and the degree of nitrate consumption (using foraminifera-bound δ15N) from six cores in the central equatorial Pacific for the Holocene (0–10,000 years ago) and the LGP (17,000–27,000 years ago). We find that, although dust deposition in the central equatorial Pacific was two to three times greater in the LGP than in the Holocene, productivity was the same or lower, and the degree of nitrate consumption was the same. These biogeochemical findings suggest that the relatively greater ice-age dust fluxes were not large enough to provide substantial iron fertilization to the central equatorial Pacific. This may have been because the absolute rate of dust deposition in the LGP (although greater than the Holocene rate) was very low. The lower productivity coupled with unchanged nitrate consumption suggests that the subsurface major nutrient concentrations were lower in the central equatorial Pacific during the LGP. As these nutrients are today dominantly sourced from the Subantarctic Zone of the Southern Ocean, we propose that the central equatorial Pacific data are consistent with more nutrient consumption in the Subantarctic Zone, possibly owing to iron fertilization as a result of higher absolute dust fluxes in this region7, 8. Thus, ice-age iron fertilization in the Subantarctic Zone would have ultimately worked to lower, not raise, equatorial Pacific productivity.
Keywords: Biogeochemistry; Palaeoceanography